The problem with faith‐based carve‐outs: RSE policy, religion and educational goods. Issue 5 (18th November 2022) - Wareham, Ruth J.
Abstract: In September 2020, relationships and sex education (RSE) became compulsory in all English secondary schools, and relationships education became compulsory in all English primary schools, marking a significant step forward in the fight to establish children's rights. Although the new RSE regime will help to ensure that many English schools provide pupils with a far more comprehensive RSE curriculum than ever before, the statutory guidance underpinning it includes a number of caveats that mean, although the subject is compulsory, not all children will receive the same content. Arguably, along with the right to withdraw (which is often exercised on religious grounds), the most insidious of these 'carve‐outs' allows faith schools to teach RSE according to their 'distinctive religious character'. This exemption has been used to defend the use of religious RSE resources that critics maintain are misogynistic, homophobic and often draw heavily on pseudoscience, as well as to justify leaving certain topics (such as same‐sex relationships or trans rights) out of classroom discussion altogether. Drawing on empirically informed normative case studies and recent reforms to the curriculum in Wales, I argue that faith‐based carve‐outs to RSE policy imperil children's access to a distinct package of educational goods. Using a recent framework for educational decision‐making based on these goods developed by Brighouse et al. I go on to conclude that such policies are politically and morally unjustifiable (at least if one agrees that the relevant package of goods is desirable). I further maintain that, even when considered from the perspective of human rights law—which is often given as a pragmatic reason to allow more permissive policies with respect to teaching topics that may impinge upon parents' deeply held convictions—there are no necessary grounds for governments to legislate for the subject to be circumscribed by the religious beliefs of parents or the faith ethos of the schools children attend.